Coupled hydro-mechanical modeling for saturated fractured rock mass by discontinuous deformation analysis - Chen, Huimei (2015)
Discontinuous Deformation Analysis (DDA) method can be applied to study the static and dynamic behavior of fractured rock masses, where the fractures are represented explicitly and assigned with independent physical parameters. In this thesis, the fracture flow approach and the dual permeability approach are introduced to model the fluid flow behaviors through the fractured rock mass based on DDA method. The fracture networks connected by major fractures are often considered as the only path for the fluid flow through the fractured rock mass. However, there are still lots of minor fractures and also pores inside the rock matrices that can conduct the fluid flow at the same time. Thus, a dual permeable media model is needed for the description of the flow behavior when the porous media exist in the rock mass. The main development work of this thesis focuses on the seepage inside the fractured rock mass with the considerations of fracture flow and the dual permeable media flow under the DDA framework, including: 1. A preliminary coupled DDA hydro-mechanical model is developed for steady flow in two dimensional fracture networks. The case studies are performed to verify the correctness and potential applications of the coupled DDA model. The numerical results show that both the flow rate and the mechanical responses for the rock blocks under the hydraulic pressure can be predicted reliably by this coupled method. 2. Using the coupled DDA hydro-mechanical model, the stability analysis for the underground rock caverns under variable geological conditions is carried out. It shows that the stability for the rock caverns also has a relationship with the block size, block shape and joint dip angles when the ground water exists. The study concludes that the underground water cannot be neglected for the stability analysis. 3. The transient fluid flow is developed and coupled into DDA. Grouting zone is taken into account for the case studies, and the hydraulic head distribution under different grouting zone sizes is studied. 4. Based on the coupled DDA hydro-mechanical model, the dual permeable media approach is developed to take the porous rock flow into consideration. The global solution method is employed to solve the seepage field when both the fracture flow and porous medium flow are considered in the domain.